2023
DOI: 10.1039/d3gc01533e
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids membranes for liquid separation: status and challenges

Abstract: Ionic liquids-based membranes (ILMs) have garnered significant attention due to the unique coordination properties offered by both ILs and membranes. This makes them a promising area of research with a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 152 publications
(228 reference statements)
0
7
0
Order By: Relevance
“…A potential two-step CO 2 adsorption mechanism was proposed, where CO 2 molecules were initially captured by the multiple amine groups of ILs to form carbamates, and then, CO 2 interacted with the basic [Ac] − sites, as reported by Ibrahim et al 66 Except for the bulk IL-MOFs monoliths, IL-MOFs could also serve as fillers to fabricate IL-based membranes, including supported ionic liquid membranes (SILMs), ionic liquid polymer membranes, or mixed matrix membranes (ILPMs or ILMMMs), as discussed in our previous review. 101 It was found that the CO 2 permeability (335 Barrer) and CO 2 / N 2 selectivity (176) were significantly improved through the incorporation of [Emim][OAc]-CuBTC into Pebax, which were 2.5-and 5.5-times that of the Pebax membrane, respectively. 67 As for the latter, the ideal CO 2 /N 2 selectivity of 1347 and CO 2 /CH 4 selectivity of 122 were found to be 45 and 10 times higher, respectively, compared to the pristine Pebax membrane.…”
Section: Il-mofs/cofs For Co 2 Capturementioning
confidence: 99%
See 1 more Smart Citation
“…A potential two-step CO 2 adsorption mechanism was proposed, where CO 2 molecules were initially captured by the multiple amine groups of ILs to form carbamates, and then, CO 2 interacted with the basic [Ac] − sites, as reported by Ibrahim et al 66 Except for the bulk IL-MOFs monoliths, IL-MOFs could also serve as fillers to fabricate IL-based membranes, including supported ionic liquid membranes (SILMs), ionic liquid polymer membranes, or mixed matrix membranes (ILPMs or ILMMMs), as discussed in our previous review. 101 It was found that the CO 2 permeability (335 Barrer) and CO 2 / N 2 selectivity (176) were significantly improved through the incorporation of [Emim][OAc]-CuBTC into Pebax, which were 2.5-and 5.5-times that of the Pebax membrane, respectively. 67 As for the latter, the ideal CO 2 /N 2 selectivity of 1347 and CO 2 /CH 4 selectivity of 122 were found to be 45 and 10 times higher, respectively, compared to the pristine Pebax membrane.…”
Section: Il-mofs/cofs For Co 2 Capturementioning
confidence: 99%
“…Except for the bulk IL-MOFs monoliths, IL-MOFs could also serve as fillers to fabricate IL-based membranes, including supported ionic liquid membranes (SILMs), ionic liquid polymer membranes, or mixed matrix membranes (ILPMs or ILMMMs), as discussed in our previous review . These kinds of composite membranes are regarded as promising candidates for CO 2 permeation and capture.…”
Section: Il-mofs/cofs For Co2 Capturementioning
confidence: 99%
“…It has been reported that in the case of SLM, viscous ILs with low solubility in water can also improve membrane stability [41]. The formation of SLM membranes containing ILs is most often based on physical methods (such as impregnation, pressure-induced, and vacuum-induced methods), which lead to the impregnation of membrane pores (the basement of the membranes could be inorganic or organic with porous structures) with ionic liquids [42]. A relatively easy and economical procedure for the formation of SLMs, the availability of a wide range of ionic liquids (possibility of conducting efficient extraction in various experimental conditions), the environmental safety of the combination of membrane techniques with ILs acting as metal ion carriers, and the urgent need to develop effective methods for the recovery of REEs from aqueous solutions have resulted in a systematically growing interest in rare earth element separation methods based on the use of ILs/SLMs.…”
Section: Recovery Of Rees With the Use Of Supported Liquid Membranesmentioning
confidence: 99%
“…These interactions enable ILs to exhibit a specific selectivity in the separation process. Accordingly, ILs have been proved to be highly potential in the separation of similar metals. The primary application of ILs for 6 Li/ 7 Li separation is the implementation of conventional imidazolium ILs with CEs. Jing’s group has done much work in the separation of 6 Li and 7 Li using systems consisting of [C n mim]­[NTf 2 ] and CEs. The partitioning of Li + is significantly enhanced as a result of the Coulombic forces between the lithium–CE complex cation and [NTf 2 ] − anion.…”
Section: Introductionmentioning
confidence: 99%